2018
DOI: 10.1097/gox.0000000000002024
|View full text |Cite
|
Sign up to set email alerts
|

Objective and Patient-reported Assessments of Skin Grafts and Keystone Flaps—A Pilot Retrospective Cohort Study

Abstract: Background:The keystone perforator island flap provides a versatile form of reconstruction. Perceived benefits include better donor-recipient color match, less contour defect, and fewer complications. To date, there has been no high-quality evidence comparing keystone flaps to split-thickness skin grafts (SSG) from both a qualitative and quantitative point of view.Methods:The Objective and Patient Reported Assessments of Skin grafts versus Keystone flap cohort study compares keystone flaps with SSGs for the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
2
9
0
2
Order By: Relevance
“…Preservation of sensation is also significantly lower in STSG than in flaps (Dobbs et al, ). The presence of contractures in the severely traumatized area is probably contributing to locally disturbed immune function (Dobbs et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Preservation of sensation is also significantly lower in STSG than in flaps (Dobbs et al, ). The presence of contractures in the severely traumatized area is probably contributing to locally disturbed immune function (Dobbs et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Four aspects were evaluated, including hematoma, epidermal erosion, skin necrosis, and wound dehiscence. Six months after surgery, the patients were asked to return to the clinic for the evaluation of the effectiveness of the operation, including odor elimination, postoperative scarring, hair growth, and patient satisfaction …”
Section: Methodsmentioning
confidence: 99%
“…Six months after surgery, the patients were asked to return to the clinic for the evaluation of the effectiveness of the operation, including odor elimination, postoperative scarring, hair growth, and patient satisfaction. [14][15][16][17][18] Unpleasant odor after axillary osmidrosis treatment was clas-…”
Section: Postoperative Evaluationmentioning
confidence: 99%
“…To this end, we recently published our own cohort study comparing objective and patient reported assessments of skin grafts versus keystone flaps (OPRASK). 5 We feel that in an era of shared decision-making it is important to consider comparisons based on patient experiences alongside traditional clinical measures of reconstruction such as healing time or complication rate. From our own experience, we would recommend the use of patient reported outcome measures (PROMs) in such studies.PROMs are standardized, validated questionnaires that are completed by patients and capture one or more aspects of their health and wellbeing.…”
mentioning
confidence: 99%
“…7 In our study we found that both general health-related quality of life, as measured using the EuroQol 5 dimension scale (EQ-5D-5L), and disease-specific quality of life, measured using the Patient and Observer Scar Assessment Scale (POSAS), were higher in those who underwent keystone flap reconstruction compared to skin grafting. 5 We thank the authors for their contribution to the important area of skin cancer reconstruction and would advocate further studies comparing reconstructive options using PROMs as a primary outcome measure.…”
mentioning
confidence: 99%